(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Autism is a complicated condition consisting of a number of behavioral and developmental aspects. In families and in society, children with autism confront a variety of obstacles. In this research the influence of autism on the family was investigated. Autism children confront several problems in development. On order to acquire an insight in tactics that they believed assisted their kid to better interaction, communication and behavior, Three autism mothers have ideas about children. Language and communications are the complementary parts of an integrated social interaction system. The research that examined autism’s parent influence, Language development and communications focused on children, children with developmental problems, communication aimed towards youngsters. Joint involvement in autism spectrum disorder (ASD), child carers, ASD, Cultural impact on children’s communication, Develop communication skills for ASD and TD youngsters, Interaction of mother-child with ASD in children